Neonatal hyperbilirubinemia and the role of unbound bilirubin - Hegyi, Thomas; Kleinfeld, Alan (The journal of maternal-fetal & neonatal medicine, 2022)
Neonatal jaundice occurs in more than 80% of newborn infants. Although mild jaundice is physiologic and possibly neuroprotective, severe hyperbilirubinemia can lead to neurologic dysfunction and death. Hyperbilirubinemia is due to an imbalance between bilirubin production and the developing excretory capacity in the first days of life. Management utilizes total serum bilirubin (TSB) levels, although recent advances suggest a role for unbound bilirubin. The goal of this review is to examine bilirubin biology, toxicology, and clinical effects, discuss preventive and therapeutic measures, describe neurodevelopmental consequences, and propose that, with the advent of new technology, unbound bilirubin is the optimal measurement for the management. Comprehensive review on neonatal hyperbilirubinemia. Neonatal hyperbilirubinemia can be prevented by tin mesoporphyrin to limit heme oxygenase activity, a key enzyme in bilirubin production, or restricting bilirubin's absorption from the gastrointestinal tract. Treatment modalities include removing bilirubin from the body by exchange transfusion, binding to immunoglobulin, or converting it to a water-soluble isomer with phototherapy. While these approaches have evolved during the past decades, the diagnosis, intervention indications, and prognosis have consistently relied on TSB concentration despite its poor ability to predict an outcome. Total serum bilirubin is inadequate to optimize care of the term and preterm infant with hyperbilirubinemia. A rapid, accurate, and more effective indicator of bilirubin neurotoxicity is needed to manage jaundiced infants and for the universal screening of newborn infants. Future measurements of free bilirubin unattached to albumin will improve the management of neonatal hyperbilirubinemia.